PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATERI PERUBAHAN SIFAT BENDA - Susilowaty, Purwanti Subekti Putri; Aeni, Ani Nur; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
Based on the preliminary observation to the 5th grade student at SDN Cipanas, a problem that showed up is the low outcome of learning result. There is 22 students but only 6 students who passed with 27,27% and 16 students not passed yet with 72,73%. It caused by the conventional learning method that used by the teacher in the learning process which make the engagement of student lacking. Seeing this condition, the researcher applied problem based learning method to resolve the problem. Method that used in this research is classroom action research and used spiral model Kemmis Taggart. This research is held in three cycle because target is achieved in the 3rd cycle. The target itself is 85%. The learning result of the student, on the cycle I level of mastery is 45,45%, 72,73% on the cycle II, and for the cycle III the result is 90,91%. Based on the data from this research, it’s proved that problem based learning could improve learning result of the 5th grade student at SDN Cipanas.